Lysophosphatidylcholine promotes intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 expression in human umbilical vein endothelial cells via an orphan G protein receptor 2-mediated signaling pathway. Issue 1 (1st January 2021) - Zhang, Qian; Zhang, Wei; Liu, Jing; Yang, Haisen; Hu, Yuxia; Zhang, Mengdi; Bai, Tuya; Chang, Fuhou
ABSTRACT: The oxLDL-based bioactive lipid lysophosphatidylcholine (LPC) is a key regulator of physiological processes including endothelial cell adhesion marker expression. This study explored the relationship between LPC and the human umbilical vein endothelial cell expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) with a particular focus on the regulation of the LPC-G2A-ICAM-1/VCAM-1 pathway in this context. We explored the LPC-inducible role of orphan G protein receptor 2 (G2A) in associated regulatory processes by using human kidney epithelial (HEK293) cells that had been transfected with pET-G2A, human umbilical vein endothelial cells (HUVECs) in which an shRNA was used to knock down G2A, and western blotting and qPCR assays that were used to confirm changes in gene expression. For in vivo studies, a rabbit model of atherosclerosis was established, with serum biochemistry and histological staining approaches being used to assess pathological outcomes in these animals. The treatment of both HEK293 cells and HUVECs with LPC promoted ICAM-1 and VCAM-1 upregulation, while incubation at a pH of 6.8 suppressed such LPC-induced adhesion marker expression. Knocking down G2A by shRNA and inhibiting NF-κB activity yielded opposite outcomes. The application of a Gi protein inhibitor had no impact on LPC-induced ICAM-1/VCAM-1 expression. Atherosclerotic model exhibited high circulating LDL and LPC levels as well as high aortic wall ICAM-1/VCAM-1 expression. Overall, these results suggested that the LPC-G2A-ICAM-1/VCAM-1 pathway may contribute to the atherogenic activity of oxLDL, with NF-κB antagonists representing potentially viable therapeutic tools for the treatment of cardiovascular disease. GRAPHICAL ABSTRACT: uf0001